Highly strained organogold complexes and their gold- or rhodium-catalyzed isomerizations - Mulks, Florian; Faraji, Shirin; Rominger, Frank; Dreuw, Andreas; Hashmi, A. Stephen K. (Chemistry - a European journal, 2018)
The synthesis and characterization of (NHC)(tricyclo[4.1.0.02,7]hept-1-yl)gold(I) compounds is reported. Several of these organometallic compounds could be obtained by transmetalation from the organolithium precursor to the corresponding (NHC)gold(I) chlorides. These are by far the most strained stable organogold compounds reported so far. With these new compounds we were able to efficiently and selectively accomplish the first gold-catalyzed rearrangement of organogold compounds, even better yields were obtained by the first rhodium-catalyzed rearrangement of these organogold species. (E/Z)-Mixtures of (NHC)(cyclohex-2-en-1-ylidenemethyl)gold(I) were obtained, none of the other known rearrangement products of tricycloheptanes. Additional insight into the chemical and physical properties of the strained compounds was obtained by spectroscopic and computational studies.
First published: 04 October 2017
Gesehen am 28.06.2018